Negative electrode material, preparation method thereof, negative electrode sheet, and battery
Patent Information
- Application Number
- CN202410873710.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2026-09-25
- Estimated Expiration
- 2044-06-28
AI Technical Summary
但常规的锂掺杂并不能有效的得到首效、高温存储的同时优化,且存储过程中的容量损失过多,会阻碍其在锂电池中的应用,因此,有必要提供一种容量、首效高,同时高温存储好的负极材料
[0029]本申请提供的负极材料包括硅基内核以及包覆于所述硅基内核的表面的碳层,硅基内核包括硅酸锂、硅,使用王水消解规定量的负极材料时所检测到的锂元素的质量含量为I1,使用HF和HNO3的混合液消解规定量的负极材料时所检测到的锂元素的质量含量为I2,I1/I2≤0.3。在此范围内,说明锂并非只掺杂在负极材料颗粒表面,而是部分分布在负极材料颗粒的内部,且内部的锂被硅或者硅氧化物保护到,在高温存储时,电解液不易分解,能够有效提升电池的高温存储性能,且能够有效抑制老化损失。
Smart Images

Figure CN121237836B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a negative electrode material and its preparation method, a negative electrode sheet, and a battery. Background Technology
[0002] As the application of lithium-ion batteries continues to expand and deepen, the requirements for their performance are also increasing, especially in terms of energy density. Traditional graphite anode materials are no longer sufficient to meet the growing market demand. As a high-specific-capacity anode material, silicon-oxygen materials have attracted much attention in recent years. Silicon-oxygen materials have a specific capacity exceeding 2000 mAh / g, but their relatively lower initial coulombic efficiency, poorer conductivity, and inferior cycle and rate performance compared to graphite materials limit their practical applications.
[0003] To improve the performance of silicon-oxygen materials, enterprises, universities, and other related institutions have developed many methods. Lithium doping can significantly improve the initial coulombic efficiency of silicon-oxygen materials. Lithium doping is not only a means to improve the initial efficiency of silicon-oxygen materials, but it also has the potential to improve high-temperature storage in battery applications and reduce aging losses. However, conventional lithium doping cannot effectively optimize both initial efficiency and high-temperature storage simultaneously, and the excessive capacity loss during storage hinders its application in lithium batteries. Therefore, it is necessary to provide a negative electrode material with high capacity, high initial efficiency, and good high-temperature storage. Summary of the Invention
[0004] This application provides a negative electrode material with excellent high-temperature storage performance and effective suppression of aging loss, as well as its preparation method, negative electrode sheet, and battery.
[0005] In a first aspect, this application provides a negative electrode material comprising a silicon-based core and a carbon layer coating the surface of the silicon-based core. The silicon-based core comprises lithium silicate and silicon. In a first ICP measurement, the mass content of lithium element detected when a predetermined amount of the negative electrode material is digested with aqua regia is I1. In a second ICP measurement, the predetermined amount of the negative electrode material is digested with a mixture of HF and HNO3, heated until the solvent is completely evaporated, cooled, and then HCl is added. After heating until the residue is completely dissolved, the mass content of lithium element detected is I2, and I1 / I2 ≤ 0.3.
[0006] In the negative electrode material provided in this application, the ratio of I1 / I2≤0.3 indicates that an appropriate amount of lithium is protected by silicon or silicon oxide, and the content of residual lithium exposed on the surface is low, making it difficult to catalyze the decomposition of the electrolyte. Therefore, the electrolyte is not easily decomposed during high-temperature storage, which can effectively improve the high-temperature storage performance of the battery and effectively suppress aging loss.
[0007] In some embodiments, the range of lithium mass content I1 measured in the first ICP measurement is I1≤4wt%, and / or the range of lithium mass content I2 measured in the second ICP measurement is 2wt%≤I2≤13.5wt%.
[0008] In some embodiments, the lithium silicate includes at least one of Li2SiO3 and Li2Si2O5.
[0009] In some embodiments, the mass content of lithium silicate in the negative electrode material is 20% to 80%, based on the mass of the negative electrode material.
[0010] In some embodiments, the silicon comprises silicon microcrystals with a size ≤20 nm. When the average size of the silicon microcrystals is too large, the expansion stress generated during lithium intercalation is uneven, which can easily lead to particle breakage of the anode material, loss of electrochemical activity, and consequently reduced product cycle performance. Therefore, controlling the average size of the silicon microcrystals within the aforementioned range is beneficial for improving the uniformity of expansion stress in the anode material particles, reducing particle breakage, and achieving an ideal balance in cycle performance, capacity utilization, and rate performance. It also effectively reduces the pulverization of the anode electrode.
[0011] In some embodiments, the mass ratio of lithium to oxygen in the negative electrode material is set as x, and the mass ratio of lithium to oxygen in the surface layer of the negative electrode material is set as y. The relationship between x and y satisfies: y / x ≤ 0.35. Here, the surface layer is defined as a layer ≤ 10 nm thick from the outer surface of the negative electrode material particle to its center. By ensuring that the relationship between x and y satisfies y / x ≤ 0.35, a large amount of lithium is protected by silicon or silicon oxide. This reduces the problem of severe electrolyte decomposition even when operating at high temperatures in batteries, thus improving the high-temperature storage performance of the battery. Furthermore, during the slurry preparation process, because a large amount of lithium is protected by silicon or silicon oxide, it is less likely to dissolve into the slurry, thus reducing problems such as slurry gas generation and sedimentation.
[0012] In some embodiments, the carbon content in the negative electrode material is 2% to 15% by mass, based on the mass of the negative electrode material. Selecting a carbon content within this range helps to improve the conductivity of the negative electrode material.
[0013] In some embodiments, the pH value of the negative electrode material is in the range of 9 to 11.
[0014] In some embodiments, the silicon-based core comprises silicon oxide, which includes silicon and oxygen elements, wherein the atomic ratio of silicon to oxygen is 0 to 2, excluding 0.
[0015] In some embodiments, the silicon-based core comprises silicon oxide with the general chemical formula SiOx, where 0 < x ≤ 2.
[0016] Secondly, this application provides a method for manufacturing a negative electrode material, comprising: step S1: performing a first carbon coating treatment on a silicon-oxygen raw material; step S2: performing a surface oxidation treatment on the silicon-oxygen raw material after the first carbon coating treatment; step S3: mixing the oxidized silicon-oxygen raw material with a lithium source and performing heat treatment to obtain a lithium-doped silicon-oxygen material; and step S4: mixing the lithium-doped silicon-oxygen material again with a carbon source and a reducing gas and performing a second carbon coating treatment to obtain a negative electrode material.
[0017] In some embodiments, the silicon-oxygen raw material is SiOy, where 0 < y ≤ 2.
[0018] In some implementations, the carbon source used in the first carbon coating process includes both gaseous and solid carbon sources.
[0019] In some embodiments, the carbon source used in the first carbon coating process includes a gaseous carbon source, which includes at least one of alkanes, cycloalkanes, alkenes, alkynes, and aromatic hydrocarbons.
[0020] In some embodiments, the carbon source used in the first carbon coating treatment includes a solid carbon source, which includes at least one of sucrose, glucose, polyethylene, polyvinyl alcohol, polyethylene glycol, polyaniline, epoxy resin, phenolic resin, furfural resin, acrylic resin, polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinyl chloride, and asphalt.
[0021] In some embodiments, the first carbon coating treatment is performed by carbonization, wherein the temperature range of the carbonization treatment is 600°C to 1000°C and the time range of the carbonization treatment is 0.5h to 10h.
[0022] In some embodiments, the oxidant used in the surface oxidation treatment step is selected from at least one of benzoyl peroxide, peracetic acid, performic acid, and methyl ethyl ketone peroxide.
[0023] In some embodiments, the lithium source includes at least one selected from lithium metal, lithium hydride, lithium carbonate, lithium hydroxide, lithium borohydride, and lithium aluminum hydride.
[0024] In some embodiments, the reducing gas includes hydrogen and methane.
[0025] In some embodiments, the carbon source in the second carbon coating step includes a gaseous carbon source, which includes at least one of alkanes, cycloalkanes, alkenes, alkynes, and aromatic hydrocarbons.
[0026] In some embodiments, after step S4, the process further includes: sieving the manufactured negative electrode material to obtain negative electrode material of a specified size.
[0027] Thirdly, this application provides a negative electrode sheet, comprising the negative electrode material described in the first aspect or the negative electrode material prepared by the preparation method described in the second aspect.
[0028] Fourthly, this application provides a battery including the negative electrode sheet described in the third aspect.
[0029] The negative electrode material provided in this application includes a silicon-based core and a carbon layer coating the surface of the silicon-based core. The silicon-based core includes lithium silicate and silicon. When a specified amount of negative electrode material is digested with aqua regia, the detected lithium content is I1; when a specified amount of negative electrode material is digested with a mixture of HF and HNO3, the detected lithium content is I2, and I1 / I2 ≤ 0.3. Within this range, it indicates that lithium is not only doped on the surface of the negative electrode material particles, but is partially distributed inside the negative electrode material particles, and the internal lithium is protected by silicon or silicon oxide. During high-temperature storage, the electrolyte is less prone to decomposition, effectively improving the high-temperature storage performance of the battery and effectively suppressing aging losses.
[0030] In the method for preparing the negative electrode material of this application, the silicon-oxygen raw material after the first carbon coating undergoes surface oxidation treatment to form some oxygen-containing groups on the surface of the carbon layer. During the lithium doping process, the oxygen-containing groups combine with lithium, which on the one hand slows down the lithium doping reaction rate, and on the other hand forms a lithium transport layer, allowing lithium to enter the particle interior more uniformly for the lithium doping reaction. This prevents the silicon generated from agglomerating due to an excessively fast lithium doping reaction and severe exothermic reaction, and also prevents lithium from being doped only on the surface of the negative electrode material particles. In addition, the second carbon coating treatment can protect some lithium from being dissolved, and the addition of a reducing gas can reduce the over-oxidized silicon back to silicon, so as not to affect the battery capacity and initial efficiency. Attached Figure Description
[0031] Figure 1 This is an electron microscope image of the negative electrode material according to one embodiment of this application.
[0032] Figure 2 This is a flowchart illustrating the manufacturing process of the negative electrode material of this application. Detailed Implementation
[0033] The technical solutions in the embodiments of this application are described clearly and in detail below. Obviously, the described embodiments are only some, not all, of the embodiments of this application. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used in the specification of this application is for the purpose of describing particular embodiments only and is not intended to limit this application.
[0034] The embodiments of this application will be described in detail below. However, this application may be embodied in many different forms and should not be construed as limited to the exemplary embodiments set forth herein. Rather, these exemplary embodiments are provided to provide a thorough and detailed understanding of this application to those skilled in the art.
[0035] Additionally, for simplicity and clarity, the dimensions or thicknesses of various components and layers may be enlarged in the accompanying drawings. Throughout the text, the same values refer to the same elements.
[0036] Furthermore, when describing the implementation of this application, the word "may" refers to "one or more implementations of this application".
[0037] The technical terms used herein are for the purpose of describing particular embodiments and are not intended to limit this application. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. It should be further understood that the term "comprising," when used in this specification, means the presence of the described features, values, steps, operations, elements, and / or components, but does not exclude the presence or addition of one or more other features, values, steps, operations, elements, components, and / or combinations thereof. A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another instance, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C.
[0038] Spatial terms, such as "above," may be used herein for convenience in describing the relationship between one element or feature and another element (or feature) or feature (or feature) illustrated in the figure. It should be understood that, in addition to the orientations depicted in the figure, spatial terms are intended to include different orientations of the device or apparatus in use or operation. For example, if the device in the figure is flipped, an element described as "above" or "on" other elements or features would be oriented "below" or "under" other elements or features. Therefore, the exemplary term "above" can include both above and below orientations.
[0039] In this application, the design relationships of greater than, less than, or not equal to parameter values need to exclude reasonable errors of the measuring equipment.
[0040] One embodiment of this application provides a battery, the battery including a positive electrode, a negative electrode, and a separator. The separator is disposed between the positive electrode and the negative electrode. The positive electrode, the separator, and the negative electrode can be alternately stacked to form a stacked electrode assembly, or the positive electrode, the separator, and the negative electrode can be stacked and then wound to form a wound electrode assembly.
[0041] The battery also includes a casing and an electrolyte (not shown), with the positive electrode, the negative electrode, the separator, and the electrolyte housed within the casing. The casing may be a packaging bag encapsulated with an encapsulation film, such as, but not limited to, aluminum-plastic film; that is, the battery may be a pouch battery. The casing may also be, but is not limited to, casings disclosed in the prior art such as steel-cased batteries and aluminum-cased batteries.
[0042] The positive electrode includes a positive current collector and a positive active layer disposed on the positive current collector. The positive current collector can be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as, but not limited to, a current collector formed by combining the aforementioned conductive foil and polymer substrate. The positive active layer contains a positive active material, which includes a compound that reversibly inserts and de-intercalates lithium ions (i.e., a lithiation intercalation compound). In some embodiments, the positive active material may include a lithium transition metal composite oxide. This lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese, and nickel. In some embodiments, the positive active material may include, but is not limited to, lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary materials (NCM), lithium manganese oxide (LiMn2O4), and lithium nickel manganese oxide (LiNi). 0.5 Mn 1.5 At least one of lithium iron phosphate (LiFePO4) or lithium iron phosphate (LiFePO4).
[0043] The positive electrode active layer also includes an adhesive to bond the positive electrode active material particles, thereby facilitating the formation of a film layer, and also improving the bonding force between the positive electrode active layer and the positive electrode current collector.
[0044] In some embodiments, the adhesive may include, but is not limited to, at least one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, sodium carboxymethyl cellulose, sodium alginate, sodium polyacrylate, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, or nylon.
[0045] The positive electrode active layer may further comprise a conductive material, which includes, but is not limited to, carbon-based materials, metal-based materials, conductive polymers, or any combination thereof. In some embodiments, the carbon-based material may include, but is not limited to, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanotubes, or any combination thereof. In some embodiments, the metal-based material may include, but is not limited to, metal powders or metal fibers, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.
[0046] The negative electrode sheet includes a negative current collector and a negative active layer disposed on the negative current collector. The negative current collector can be at least one of copper foil, nickel foil, stainless steel foil, titanium foil, or carbon-based current collector, or any composite current collector disclosed in the prior art, such as, but not limited to, a current collector formed by combining the aforementioned conductive foil and polymer substrate.
[0047] The negative electrode active layer includes a negative electrode material. An electron micrograph of the negative electrode material according to one embodiment of this application is shown below. Figure 1 As shown. In embodiments of this application, the negative electrode material includes a silicon-based core and a carbon layer covering the surface of the silicon-based core, wherein the silicon-based core includes lithium silicate and silicon.
[0048] When testing the lithium content in the negative electrode material, the test method employs two ICP methods: a first ICP measurement and a second ICP measurement. In the first ICP measurement, the lithium content detected after digesting a specified amount of negative electrode material with aqua regia is I1. In the second ICP measurement, a specified amount of negative electrode material is digested with a mixture of HF and HNO3, heated until the solvent is completely evaporated, cooled, and then HCl is added. The lithium content detected after heating until the residue is completely dissolved is I2, where I1 / I2 ≤ 0.3. Specifically, I1 / I2 can be 0.1, 0.15, 0.2, 0.25, 0.3, or any value within the range of any two of the above values.
[0049] In the first ICP measurement, the specific method of digestion with aqua regia was as follows: 0.500g of the negative electrode material was placed in a clean platinum crucible and then calcined in a muffle furnace under air atmosphere at 750°C for 2 hours to completely remove carbon. Then, the cooled calcination residue was taken and digested with 8ml of aqua regia and 5ml of ultrapure water in a graphite digester at 130°C for 30 minutes. The digested solution was then diluted to 100mL in a plastic volumetric flask. Finally, the mass content of lithium (I1) was tested using an ICP spectrometer (Agilent 5800VDV ICP-OES).
[0050] In the second ICP measurement, the specific method for digestion using a mixture of HF and HNO3 was as follows: 0.500g of the negative electrode material was placed in a clean platinum crucible and then calcined in a muffle furnace under air atmosphere at 750°C for 2 hours to completely remove carbon. The cooled calcined residue was then reacted thoroughly with a mixture of 4mL HNO3 and 6mL HF. Next, the platinum crucible containing this solution was placed on a 350°C hot plate until the solvent was completely evaporated. After the crucible cooled, 6mL HCl was added, and the mixture was heated until the residue was completely dissolved. The solution was then taken and diluted to a 100mL plastic volumetric flask. Finally, the lithium content (I2) was measured using an ICP spectrometer (Agilent 5800VDV ICP-OES).
[0051] In some embodiments, the lithium content I1 measured in the first ICP measurement ranges from I1 ≤ 4 wt%, for example, it can be 0.1 wt%, 0.5 wt%, 1.2 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, or any value between them. The lithium content I2 measured in the second ICP measurement ranges from 2 wt% ≤ I2 ≤ 13.5 wt%, for example, it can be 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13.5 wt%, or any value between them. It can be understood that by selecting I1 and I2 within the above ranges, it is beneficial to improve the first-stage efficiency and capacity of the anode material. If the values of I1 and I2 are too high, the capacity of the anode material is low; if the value of I2 is too low, the first-stage efficiency of the anode material is low.
[0052] In some embodiments, lithium silicate includes at least one of Li2SiO3 and Li2Si2O5.
[0053] In some embodiments, the silicon-based core comprises silicon oxide with the general chemical formula SiOx, where 0 < x ≤ 2, and x can take the values of 0.1, 0.3, 0.5, 0.8, 1.0, 1.2, 1.5, 1.8, 1.95, 2 or any value between them.
[0054] In some embodiments, the silicon-based core comprises silicon oxide, which comprises silicon and oxygen elements, wherein the atomic ratio of silicon to oxygen is 0 to 2, excluding 0, and the atomic ratio may be 0.1, 0.3, 0.5, 0.8, 1.0, 1.2, 1.5, 1.8, 1.95, 2 or any value therebetween.
[0055] It is understandable that in the first ICP measurement, when using a mixed solution of HCl and HNO3 (i.e., aqua regia) to digest the negative electrode material of this application, aqua regia cannot dissolve silicon or silicon oxide. Therefore, even when some lithium elements are surrounded and protected by silicon or silicon oxide, these protected lithium elements are difficult to dissolve by acid and thus difficult to detect. In contrast, in the second ICP measurement, when a mixed solution of HF and HNO3 is used for digestion, HF can dissolve silicon or silicon oxide. Therefore, even if some lithium elements are protected by silicon or silicon oxide, these lithium elements can be dissolved and detected. Therefore, by comparing the mass content of lithium elements detected by the two methods, the distribution of lithium elements can be understood.
[0056] In the negative electrode material provided in this application, the ratio I1 / I2 ≤ 0.3 indicates that lithium is not only doped on the surface of the negative electrode material particles, but is partially distributed inside the particles. Furthermore, if the lithium distribution is uneven, the cycle performance of the negative electrode material is poor, while the cycle performance of the negative electrode material in this application is excellent, indicating that the lithium is uniformly distributed inside the negative electrode material particles. Moreover, the internal lithium is protected by silicon or silicon oxide, and the content of protected lithium is greater than or equal to 0.7%, resulting in less residual lithium exposed on the surface. This makes it less prone to catalytic decomposition of the electrolyte. Therefore, during high-temperature storage, the electrolyte is less likely to decompose, effectively improving the high-temperature storage performance of the battery and effectively suppressing aging losses.
[0057] In some embodiments, the mass ratio of lithium to oxygen in the negative electrode material is set as x, and the mass ratio of lithium to oxygen on the surface of the negative electrode material is set as y. The relationship between x and y satisfies: y / x≤0.35, where the surface layer is defined as a layer ≤10nm thick from the outer surface of the negative electrode material particle to the center of the negative electrode material particle.
[0058] By ensuring that the relationship between x and y satisfies y / x≤0.35, during the process of preparing the negative electrode material into a slurry, because a large amount of lithium in the negative electrode material is protected by silicon or silicon oxide, the lithium in the negative electrode material is not easily dissolved into the slurry. Therefore, problems such as slurry gas generation and sedimentation are less likely to occur.
[0059] In some embodiments, the lithium content in the negative electrode material is 0.1wt% to 20wt% based on the weight of the negative electrode material, for example, 0.1wt%, 1wt%, 3wt%, 5wt%, 7wt%, 10wt%, 12wt%, 15wt%, 18wt%, 20wt%, or any value within the range of any two of the above values.
[0060] In some embodiments, the oxygen content in the negative electrode material ranges from 20wt% to 40wt%, based on the weight of the negative electrode material, for example, 20wt%, 22wt%, 25wt%, 28wt%, 30wt%, 32wt%, 35wt%, 38wt%, 40wt%, or any value within the range of any two of the above values.
[0061] In some embodiments, the lithium silicate content in the negative electrode material is 20% to 80% by mass, for example, 20%, 30%, 40%, 50%, 60%, 70%, 80%, or any value within the range of any two of the above values. Selecting such a range is beneficial for improving the battery's initial efficiency.
[0062] In some embodiments, the carbon content in the negative electrode material is 2% to 10% by mass, for example, 2%, 4%, 6%, 8%, 10%, or any value within the range of any two of the above values. Selecting a carbon content within this range helps to improve the conductivity of the negative electrode material.
[0063] In some embodiments, the silicon comprises silicon microcrystals with a size ≤20 nm, specifically, for example, 1 nm, 3 nm, 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 18 nm, 20 nm, or any value within the range of any two of the above values. When the average size of the silicon microcrystals is too large, the expansion stress generated during lithium intercalation is uneven, which can easily lead to the breakage of the negative electrode material particles, loss of electrochemical activity, and thus reduced product cycle performance. Therefore, controlling the average size of the silicon microcrystals within the above range is beneficial to improving the uniformity of expansion stress of the negative electrode material particles, reducing particle breakage, and enabling the negative electrode material to achieve an ideal balance in cycle performance, capacity utilization, and rate performance, while also effectively reducing the pulverization of the negative electrode sheet.
[0064] The pH value of the negative electrode material is 9 to 11, for example 9, 10, 11 or any value within the range of any two of the above values.
[0065] The negative electrode active layer also includes a binder to bond the negative electrode material particles, thereby facilitating the formation of a film layer, and can also improve the bonding force between the negative electrode active layer and the negative electrode current collector.
[0066] In some embodiments, the adhesive may include, but is not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, sodium carboxymethyl cellulose, sodium alginate, sodium polyacrylate, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, or nylon, etc.
[0067] The negative electrode active layer may further include a conductive material, which includes, but is not limited to, carbon-based materials, metal-based materials, conductive polymers, or any combination thereof. In some embodiments, the carbon-based material may include, but is not limited to, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanotubes, or any combination thereof. In some embodiments, the metal-based material may include, but is not limited to, metal powders or metal fibers, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.
[0068] The separator membrane includes a membrane layer with a porous structure, and its material includes, but is not limited to, at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide, or aramid. For example, the separator membrane may be a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane, etc.
[0069] The electrolyte can be in one or more of the following states: gel, solid, and liquid. In some embodiments, the liquid electrolyte includes a lithium salt and an organic solvent. The lithium salt may be selected from, but is not limited to, one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium tetraphenylborate (LiB(C6H5)4), lithium methanesulfonate (LiCH3SO3), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiN(SO2CF3)2), lithium tris(trifluoromethanesulfonyl)methyllithium (LiC(SO2CF3)3), lithium dioxolaneborate (LiBOB), and lithium difluorophosphate (LiPO2F2). For example, LiPF6 is selected as the lithium salt because it provides high ionic conductivity and improves cycling characteristics. The organic solvent may be a carbonate compound, a carboxylic acid ester compound, or an ether. Compounds, nitrile compounds, other organic solvents, or combinations thereof. Examples of carbonate compounds include, but are not limited to, diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, or combinations thereof.
[0070] The aforementioned battery is used in electronic devices to power other electronic components within those devices. Because the negative electrode material in the battery improves cycle performance and energy density, it contributes to extending the lifespan of the electronic device.
[0071] The electronic devices may include, but are not limited to, laptops, pen-based computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium-ion capacitors, etc.
[0072] like Figure 2 As shown, this application provides a method for preparing a negative electrode material, which includes the following steps: Step S1: Perform the first carbon coating treatment on the silicon-oxygen raw material.
[0073] Specifically, silicon-oxygen raw materials are mixed with a carbon source and subjected to carbonization treatment to achieve the first carbon coating treatment.
[0074] In some embodiments, the general chemical formula of the silicon-oxygen raw material is SiOy, where 0 < y ≤ 2. For example, y can be 0.1, 0.5, 0.8, 1, 1.5, 1.8, 2, or any value within the range of any two of the above values.
[0075] It is understood that the silicon-oxygen raw material can be purchased commercially or produced by reacting Si and SiO2 raw materials; no limitation is made here.
[0076] In some embodiments, the carbon coating amount in the first carbon coating treatment ranges from 1 wt% to 9 wt%. By selecting a carbon coating amount within this range, it is beneficial to improve the conductivity and capacity of the anode material. If the carbon coating amount in the first carbon coating treatment is too low, the conductivity of the anode material will be poor; if it is too high, the capacity of the anode material will be low.
[0077] In some embodiments, the carbon source includes gaseous carbon sources and solid carbon sources. In some embodiments, the gaseous carbon source includes, but is not limited to, at least one selected from alkanes, cycloalkanes, alkenes, alkynes, and aromatic hydrocarbons. In some embodiments, the solid carbon source includes, but is not limited to, at least one selected from sucrose, glucose, polyethylene, polyvinyl alcohol, polyethylene glycol, polyaniline, epoxy resin, phenolic resin, furfural resin, acrylic resin, polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinyl chloride, and asphalt.
[0078] The carbonization temperature is 600℃~1000℃, and the carbonization time is 0.5h~10h. In some embodiments, the carbonization temperature can be 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, or any value within the range of any two of the above values, and the carbonization time can be 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or any value within the range of any two of the above values.
[0079] It is understandable that different carbon sources require different temperatures and carbonization times.
[0080] Step S2: Perform surface oxidation treatment on the silicon-oxygen raw material that has undergone the first carbon coating.
[0081] Specifically, an oxidizing agent is used to surface-oxidize the silicon-oxygen raw material that has undergone the first carbon coating. In some embodiments, the oxidizing agent includes, but is not limited to, at least one of benzoyl peroxide, peracetic acid, performic acid, and methyl ethyl ketone peroxide. By using the above-mentioned mild oxidizing agent to slowly oxidize the silicon-oxygen raw material after the first carbon coating, the oxidation uniformity can be effectively improved and the degree of oxidation reaction can be easily controlled, making it less likely to cause silicon oxidation.
[0082] In some embodiments, the concentration of the oxidant in the reaction liquid ranges from 10% to 20%, specifically 10%, 12%, 14%, 16%, 18%, 20%, or any value within the range of any two of the above values. The oxidation time ranges from 2 to 12 hours, specifically 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, or any value within the range of any two of the above values. It is understood that the required time will vary depending on the concentration of the oxidant used.
[0083] Understandably, if the concentration of the oxidant is too low or the oxidation time is too short, the thickness of the oxide layer formed on the particle surface will not be sufficient to buffer and regulate the lithium doping reaction, which may result in a high lithium content on the surface of the anode material. In addition, if the concentration of the oxidant is too high, the efficiency improvement of the oxidation reaction will be small, but the cost of the oxidant will be too high, resulting in a low cost-performance ratio.
[0084] In some implementations, water or ether solvents, such as diethyl ether, are used as the solvent.
[0085] Furthermore, an inert gas is introduced during the surface oxidation process to reduce the participation of oxygen in the silicon oxidation. This inert gas can be, but is not limited to, at least one of nitrogen, argon, and helium.
[0086] In some implementations, the flow rate of the inert gas is in the range of 1 L / min to 10 L / min. If the flow rate is too high, it is easy to carry away the silicon-oxygen raw materials and cause waste. If the flow rate is too low, oxygen in the air is likely to participate in the oxidation of silicon.
[0087] In step S2 above, by performing surface oxidation treatment on the silicon-oxygen raw material after the first carbon coating, some oxygen-containing groups are formed on the surface of the carbon layer. During the lithium doping process, the oxygen-containing groups will combine with lithium. On the one hand, this can slow down the lithium doping reaction rate, and on the other hand, it can form a lithium transport layer, so that lithium can be doped more uniformly inside the particles. This will prevent silicon from agglomerating due to the lithium doping reaction being too fast and the heat generated being too severe, and will also prevent lithium from being doped only on the surface of the negative electrode material particles.
[0088] Step S3: Mix the oxidized silicon-oxygen raw material with a lithium source and perform heat treatment to obtain lithium-doped silicon-oxygen material.
[0089] In some embodiments, the lithium source includes, but is not limited to, at least one of lithium metal, lithium hydride, lithium carbonate, lithium hydroxide, lithium borohydride, and lithium aluminum hydride.
[0090] In one embodiment, the lithium content in the lithium source ranges from 2% to 13.5%, for example, 2%, 6%, 8%, 10%, 13.5%, or any value within the range of any two of the above values.
[0091] In some embodiments, the temperature range of the heat treatment is 400℃ to 900℃, specifically 400℃, 450℃, 500℃, 600℃, 700℃, 800℃, 900℃ or any value within the range of any two of the above values, and the time range of the heat treatment is 4h to 12h, specifically 4h, 6h, 8h, 10h, 12h or any value within the range of any two of the above values.
[0092] Step S4: The lithium-doped silicon-oxygen material is mixed again with the carbon source and reducing gas and subjected to a second carbon coating treatment to obtain the anode material.
[0093] In some embodiments, the carbon coating amount in the second carbon coating treatment is 1% to 5%, for example, it can be 1%, 2%, 3%, 4%, 5%, or any value within the range of any two of the above values. By selecting the carbon coating amount in the second carbon coating treatment within this range, it is beneficial to improve the conductivity and capacity of the negative electrode material. If the carbon coating amount is too low, the conductivity of the negative electrode material will be poor; if the carbon coating amount is too high, the capacity of the negative electrode material will be low.
[0094] The carbon source includes a gaseous carbon source, which includes at least one of alkanes, cycloalkanes, alkenes, alkynes, and aromatic hydrocarbons. A secondary carbon coating treatment can protect some lithium from dissolution, while the addition of a reducing gas can reduce the over-oxidized silicon back to silicon, ultimately without affecting the battery's capacity and initial efficiency.
[0095] In some embodiments, the reducing gas includes, but is not limited to, hydrogen and methane. In some embodiments, the flow rate of the reducing gas ranges from 0.02 L / min to 0.5 L / min, for example, it can be 0.02 L / min, 0.1 L / min, 0.2 L / min, 0.3 L / min, 0.4 L / min, 0.5 L / min, or any value within the range of any two of the above values. Selecting this range helps improve the reduction effect and avoids waste. If the flow rate of the reducing gas is too low, the reduction effect is poor and the capacity of the negative electrode material is low; if the flow rate of the reducing gas is too high, there are safety risks and waste occurs.
[0096] In some embodiments, the carbonization temperature is 600℃~1000℃, and the carbonization time is ≥2h. In some embodiments, the carbonization temperature can be 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, or any value within the range of any two of the above values, and the carbonization time can be 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or any value within the range of any two of the above values.
[0097] Furthermore, in some embodiments, after step S4, the manufactured negative electrode material is further sieved to obtain negative electrode material of a specified size.
[0098] In some embodiments, the screening method includes at least one of a fixed screen, a drum screen, a resonant screen, a roller screen, a vibrating screen, and a chain screen, and the mesh size of the screening is ≥200 mesh.
[0099] In the preparation method of the negative electrode material of this application, the silicon-oxygen raw material after the first carbon coating is subjected to surface oxidation treatment to form some oxygen-containing groups on the surface of the carbon layer. During the lithium doping process, the oxygen-containing groups combine with lithium, which can slow down the lithium doping reaction on the one hand, and form a lithium transport layer on the other hand, so that lithium can enter the particle interior more uniformly for lithium doping reaction. It will not cause silicon aggregation due to excessively fast lithium doping reaction and severe exothermic reaction, nor will it cause lithium to be doped only on the surface of the negative electrode material particles. Thus, most of the lithium is surrounded and protected by silicon or silicon oxide, thereby making I1 / I2 ≤ 0.3. In addition, the second carbon coating treatment can protect some lithium from being dissolved, and the addition of reducing gas can reduce the over-oxidized silicon back to silicon, so as not to affect the battery capacity and first efficiency.
[0100] Example 1 1. Take 2 kg of SiO powder, place it in a tube furnace and heat it to 850°C under nitrogen protection. Then, introduce acetylene, keep it at this temperature for 4 hours, and then cool it to obtain carbon-coated SiO material. In this step, the carbon coating amount is 3.1%. 2. In a plastic beaker, prepare 3000ml of 15% peracetic acid aqueous solution. After continuously purging nitrogen gas for 10min, add the carbon-coated SiO material from step 1 to the solution and stir the reaction for 8 hours. During the process, keep nitrogen gas (flow rate: 3L / min) purging. After the reaction is complete, filter to obtain powder material and dry at 100℃ for 24h. 3. Take 110g of LiH and 1kg of the powder material obtained in step 2 and mix them. Then place them in a box furnace under nitrogen protection, heat to 780℃, and keep warm for 5 hours to obtain the powder material. 4. Take the material obtained in step 3, place it in a tube furnace and heat it to 850°C under nitrogen and hydrogen (flow rate 0.05 L / min) conditions, introduce acetylene, keep it at the temperature for 2 hours and then cool it. In this step, the carbon coating amount is 5.0%, and then the material is obtained by sieving.
[0101] Example 2 1. Take 2 kg of SiO powder, place it in a tube furnace and heat it to 850°C under nitrogen protection. Then, introduce acetylene, keep it at this temperature for 4 hours, and then cool it to obtain carbon-coated SiO material. In this step, the carbon coating amount is 3.2%. 2. In a plastic beaker, prepare 3000ml of 15% peroxyformic acid aqueous solution. After continuously purging nitrogen gas for 10min, add the carbon-coated SiO material from step 1 to the solution and stir to react for 8 hours. During the process, keep nitrogen gas (flow rate: 3L / min) purging. After the reaction is complete, filter to obtain powder material and dry at 100℃ for 24h. 3. Take 110g of LiH and 1kg of the powder material obtained in step 2 and mix them. Then place them in a box furnace under nitrogen protection, heat to 780℃, and keep warm for 5 hours to obtain the powder material. 4. Take the material obtained in step 3 and place it in a tube furnace. Heat it to 850°C under nitrogen and hydrogen (flow rate 0.05 L / min) conditions. Introduce acetylene and keep it at this temperature for 2 hours. Then cool it. In this step, the carbon coating amount is 4.9%. After sieving, the negative electrode material is obtained.
[0102] Example 3 1. Take 2 kg of SiO powder, place it in a tube furnace and heat it to 850°C under nitrogen protection. Then, introduce acetylene, keep it at this temperature for 4 hours, and then cool it to obtain carbon-coated SiO material. In this step, the carbon coating amount is 2.8%. 2. Prepare 3000ml of 15% benzoyl peroxide diethyl ether solution in a plastic beaker. After continuously purging nitrogen gas for 10 minutes, add the carbon-coated SiO material from step 1 to the solution and stir the reaction for 8 hours. During the process, keep nitrogen gas flowing in (flow rate: 3L / min). After the reaction is complete, filter to obtain powder material and dry at 100℃ for 24 hours. 3. Take 110g of LiH and 1kg of the powder material obtained in step 2 and mix them. Then place them in a box furnace under nitrogen protection, heat to 780℃, and keep warm for 5 hours to obtain the powder material. 4. Take the material obtained in step 3, place it in a tube furnace and heat it to 850°C under nitrogen and hydrogen (flow rate 0.05 L / min) conditions, introduce acetylene, keep it at the temperature for 2 hours and then cool it. In this step, the carbon coating amount is 5.1%, and then the material is obtained by sieving.
[0103] Example 4 1. Take 2 kg of SiO powder, place it in a tube furnace and heat it to 850°C under nitrogen protection. Then, introduce acetylene, keep it at this temperature for 4 hours, and then cool it to obtain carbon-coated SiO material. In this step, the carbon coating amount is 3.0%. 2. Prepare 3000ml of 15% methyl ethyl ketone peroxide ethyl ether solution in a plastic beaker. After continuously purging nitrogen gas for 10 minutes, add the carbon-coated SiO material from step 1 to the solution and stir the reaction for 8 hours. During the process, keep nitrogen gas purging (flow rate: 3L / min). After the reaction is complete, filter to obtain powder material and dry at 100℃ for 24 hours. 3. Take 110g of LiH and 1kg of the powder material obtained in step 2 and mix them. Then place them in a box furnace under nitrogen protection, heat to 780℃, and keep warm for 5 hours to obtain the powder material. 4. Take the material obtained in step 3 and place it in a tube furnace. Heat it to 850°C under nitrogen and hydrogen (flow rate 0.05 L / min) conditions. Introduce acetylene and keep it at this temperature for 2 hours. Then cool it. In this step, the carbon coating amount is 5.3%. After sieving, the negative electrode material is obtained.
[0104] Example 5 1. Take 2 kg of SiO powder, place it in a tube furnace and heat it to 850°C under nitrogen protection. Then, introduce acetylene, keep it at this temperature for 4 hours, and then cool it to obtain carbon-coated SiO material. In this step, the carbon coating amount is 2.9%. 2. In a plastic beaker, prepare 3000ml of 20% peracetic acid aqueous solution. After continuously purging nitrogen gas for 10min, add the carbon-coated SiO material from step 1 to the solution and stir the reaction for 6 hours. During the process, keep nitrogen gas (flow rate: 3L / min) purging. After the reaction is complete, filter to obtain powder material and dry at 100℃ for 24h. 3. Take 110g of LiH and 1kg of the powder material obtained in step 2 and mix them. Then place them in a box furnace under nitrogen protection, heat to 780℃, and keep warm for 5 hours to obtain the powder material. 4. Take the material obtained in step 3 and place it in a tube furnace. Heat it to 850°C under nitrogen and hydrogen (flow rate 0.05 L / min) conditions. Introduce acetylene and keep it at this temperature for 3 hours. Then cool it. In this step, the carbon coating amount is 5.2%. After sieving, the negative electrode material is obtained.
[0105] Example 6 1. Take 2 kg of SiO powder, place it in a tube furnace and heat it to 850°C under nitrogen protection. Then, introduce acetylene, keep it at this temperature for 4 hours, and then cool it to obtain carbon-coated SiO material. In this step, the carbon coating amount is 3.1%. 2. In a plastic beaker, prepare 3000ml of 10% peracetic acid aqueous solution. After continuously purging nitrogen gas for 10min, add the carbon-coated SiO material from step 1 to the solution and stir to react for 12 hours. During the process, keep nitrogen gas (flow rate: 3L / min) purging. After the reaction is complete, filter to obtain powder material and dry at 100℃ for 24h. 3. Take 110g of LiH and 1kg of the powder material obtained in step 2 and mix them. Then place them in a box furnace under nitrogen protection, heat to 780℃, and keep warm for 5 hours to obtain the powder material. 4. Take the material obtained in step 3, place it in a tube furnace and heat it to 850°C under nitrogen and hydrogen (flow rate 0.05 L / min) conditions, introduce acetylene, keep it at the temperature for 5 hours and then cool it. In this step, the carbon coating amount is 5.0%, and then the material is obtained by sieving.
[0106] Comparative Example 1 1. Take 2 kg of SiO powder, place it in a tube furnace and heat it to 850°C under nitrogen protection. Then, introduce acetylene, keep it at this temperature for 4 hours, and then cool it to obtain carbon-coated SiO material. In this step, the carbon coating amount is 3.0%. 2. Take 110g of LiH and 1kg of carbon-coated SiO material obtained in step 1 and mix them. Then place them in a box furnace under nitrogen protection, heat to 780℃, keep warm for 5 hours, and then sieve to obtain the negative electrode material.
[0107] Comparative Example 2 1. Take 2 kg of SiO powder, place it in a tube furnace and heat it to 850°C under nitrogen protection. Then, introduce acetylene, keep it at this temperature for 4 hours, and then cool it to obtain carbon-coated SiO material. In this step, the carbon coating amount is 3.2%. 2. In a plastic beaker, prepare 3000ml of 15% peracetic acid aqueous solution. After continuously purging nitrogen gas for 10min, add the carbon-coated SiO material from step 1 to the solution and stir the reaction for 8 hours. During the process, keep nitrogen gas (flow rate: 3L / min) purging. After the reaction is complete, filter to obtain powder material and dry at 100℃ for 24h. 3. Take 110g of LiH and 1kg of the powder material obtained in step 2 and mix them. Then place them in a box furnace under nitrogen protection, heat to 780℃, keep warm for 5 hours, cool and then sieve to obtain the negative electrode material. In this step, the carbon coating amount is 2.9%.
[0108] Comparative Example 3 1. Take 2 kg of SiO powder, place it in a tube furnace and heat it to 850°C under nitrogen protection. Then, introduce acetylene, keep it at this temperature for 4 hours, and then cool it to obtain carbon-coated SiO material. In this step, the carbon coating amount is 2.9%. 2. In a plastic beaker, prepare 3000 ml of 8% peracetic acid aqueous solution. After continuously purging nitrogen gas for 10 min, add the carbon-coated SiO material from step 1 to the solution and stir to react for 12 hours. During the process, keep nitrogen gas (flow rate: 3 L / min) purging. After the reaction is complete, filter to obtain powder material and dry at 100℃ for 24 h. 3. Take 110g of LiH and 1kg of the powder material obtained in step 2 and mix them. Then place them in a box furnace under nitrogen protection, heat to 780℃, and keep warm for 5 hours to obtain the powder material. 4. Take the material obtained in step 3, place it in a tube furnace and heat it to 850°C under nitrogen and hydrogen conditions (flow rate 0.05 L / min), introduce acetylene, keep it at this temperature for 2 hours and then cool it. In this step, the carbon coating amount is 5.2%, and then the material is obtained by sieving.
[0109] Performance testing methods: I. ICP method for testing lithium content in materials: ① First ICP measurement method: 0.500g of negative electrode material was placed in a clean platinum crucible and then calcined in a muffle furnace under air atmosphere at 750℃ for 2 hours to completely remove carbon. The cooled calcination residue was then mixed with 8ml of aqua regia and 5ml of ultrapure water and digested in a graphite digester at 130℃ for 30min. The solution was then taken and diluted to a 100mL plastic volumetric flask. Finally, the lithium content of the material was tested using an ICP spectrometer (Agilent 5800VDV ICP-OES).
[0110] ② Second ICP measurement method: 0.500g of negative electrode material was placed in a clean platinum crucible and then calcined in a muffle furnace under air atmosphere at 750℃ for 2 hours to completely remove carbon. The cooled calcined residue was fully reacted with a mixed acid of 4mL HNO3 and 6mL HF. The platinum crucible containing the solution was then placed on a 350℃ hot plate until the solvent was completely evaporated. After the crucible cooled, 6mL HCl was added and heated until the residue was completely dissolved. The solution was then taken and diluted to a 100mL plastic volumetric flask. Finally, the lithium content of the material was tested using an ICP spectrometer (Agilent 5800VDV ICP-OES).
[0111] II. Calculation of the mass content of lithium and oxygen in anode materials The total oxygen content of the negative electrode material was tested using an ONH elemental analyzer (ONH-2000). The specific procedure was as follows: 10-13 mg of active material was weighed, wrapped in nickel foil, and then placed into a graphite crucible within the ONH elemental analyzer for testing. The mass content of lithium, x, was calculated using the above data combined with the lithium content measured by the second ICP method.
[0112] III. Calculation of the mass ratio of lithium to oxygen in the surface layer of the negative electrode material The mass content of lithium and oxygen in the surface layer of the anode material was measured using X-ray photoelectron spectroscopy (ThermoScientific K-Alpha). The excitation source used was AlKα rays with a beam size of 400 μm. The pass energy for the full spectrum scan was 100 eV with a step size of 1 eV. Finally, the mass ratio y of lithium and oxygen in the full spectrum scan data was analyzed using Avantage software.
[0113] IV. Test method for the mass content of lithium silicate XRD analysis of the material was performed using a Panacol X'pert Pro X-ray diffractometer, with MgO as an internal standard, to quantitatively analyze the lithium silicate content. First, XRD patterns were obtained using the Panacol X'pert Pro X-ray diffractometer. Then, Jade software was used for background subtraction, smoothing, and peak finding, followed by fitting analysis. The lithium silicate content was calculated by comparing the results with the MgO content.
[0114] V. Electrochemical Performance Testing (1) First Coulomb efficiency test a. Preparation of lithium-ion batteries: The composite materials prepared in the above examples and comparative examples are used as negative electrode active materials. The conductive carbon black and CMC / SBR are mixed evenly at a mass ratio of 75:15:10 and coated on copper foil to prepare a negative electrode sheet. A lithium metal sheet is used as a positive electrode sheet and PP / PE is used as a separator to make a button battery.
[0115] b. The battery was tested using a Landon Newway 5V / 10mA battery tester. The voltage was 1.5V and the current was 0.1C. The initial coulombic efficiency was calculated as the initial charge specific capacity / the initial discharge specific capacity.
[0116] (2) Storage performance test a. Preparation of lithium-ion batteries: Silicon oxide and graphite composites were used as the negative electrode active material at a capacity of 450 mAh / g. The negative electrode sheet was prepared according to the formula: active material: CMC (2200): SP: SWCNT: SBR (BM451B) = 95.1: 1.4: 1.45: 0.05: 2.0. The positive electrode was prepared using the high-nickel NMC product M2-C2 (produced by BTR), according to the formula: M2-C2: Solef 5130: Super P: GNLC-05 = 96.6: 1.4: 1.3: 0.7. The positive and negative electrode sheets were then wound into 554065 model soft-pack cells. The cells underwent liquid injection, formation, and capacity testing to create batteries for testing. The electrode design parameters were: positive electrode compaction 3.4 g / cc, negative electrode compaction 1.65 g / cc, and negative electrode areal density 200 g / m³. 2The N / P ratio is designed to be 8.2%.
[0117] b. After cell capacity assessment, charge to 100% SOC at 0.5C, then store at 60℃ for 7 days, and discharge to the lower limit voltage at 0.5C, recording capacity 1. Then charge and discharge the battery for one week, recording the discharged capacity as capacity 2. Battery capacity 1 / initial capacity = capacity retention rate, battery capacity 2 / initial capacity = capacity recovery rate, 1 - capacity recovery rate = irreversible capacity loss rate.
[0118] (3) Aging loss test A composite of silicon oxide and graphite was used as the negative electrode active material at a capacity of 450 mAh / g. The negative electrode sheet was prepared according to the formula: active material: CMC (2200): SP: SWCNT: SBR (BM451B) = 95.1:1.4: 1.45:0.05: 2.0. The positive electrode was prepared using high-nickel NMC product M2-C2 (produced by BTR) with a formula: M2-C2: Salef 5130: Super P: GNLC-05 = 96.6:1.4:1.3:0.7. The positive and negative electrode sheets were then wound to form a 554065 model soft-pack battery cell. After liquid injection and formation, the cell was left to stand at 45℃ for 48 hours and charged to 4.2V at 0.33C. The charged capacity was recorded as C1. The battery formation process is as follows: ① 0.02C constant current charging for 30 minutes; ② 0.05C constant current charging for 30 minutes; ③ 0.1C constant current charging for 120 minutes; ④ 0.2C constant current charging for 240 minutes, with the cutoff voltage set at 4.2V; ⑤ 4.2V constant voltage cutoff current of 0.05C. The capacity charged during the battery formation stage is denoted as C0. Aging loss rate = C1 / C0.
[0119] (4) 50-week cycle retention test The negative electrode materials prepared in the above embodiments and comparative examples are mixed with graphite at a mass ratio of 10:90 to form a composite negative electrode material. Then, the composite negative electrode active material, conductive carbon black, hydroxymethyl cellulose and styrene-butadiene rubber are mixed evenly at a mass ratio of 92:4:2:2 and coated on copper foil to prepare a negative electrode sheet. A lithium metal sheet is used as a positive electrode sheet and polyethylene is used as a separator to make a button battery. The battery was tested using a Landon Newway 5V / 10mA battery tester at a voltage of 1.5V and a current of 0.1C. The 50-cycle retention rate was calculated as the ratio of the specific capacity at the 50th discharge to the specific capacity at the first discharge.
[0120] Table 1: Relevant parameters of the negative electrode materials of Examples 1-6 and Comparative Examples 1-3 Table 2: Electrochemical performance characterization of the negative electrode materials of Examples 1-6 and Comparative Examples 1-3 The results in Tables 1 and 2 demonstrate that in Examples 1-6, surface oxidation treatment of the SiO powder after the first carbon coating forms some oxygen-containing groups on the surface of the carbon layer. During the lithium doping process, the oxygen-containing groups combine with lithium, which can slow down the lithium doping reaction and form a lithium transport layer, allowing lithium to be more uniformly doped inside the particles. This allows the internal lithium to be protected by silicon or silicon oxide, resulting in high storage capacity retention even when stored in a high-temperature environment. Furthermore, it exhibits high capacity retention after 50 cycles, low aging loss, and high slurry stability.
[0121] The negative electrode material prepared in Comparative Example 1, without surface oxidation treatment, directly underwent lithium doping. The I1 / I2 value was 0.95, much greater than 0.3, and the y / x value was 0.61, much greater than 0.35. This indicates that very little lithium was protected by silicon or silicon oxide. During the pre-lithiation process, most of the lithium was doped into the surface layer of the negative electrode material. Therefore, during the slurry preparation process, most of the lithium in the negative electrode material hydrolyzed into the slurry, resulting in poor slurry stability, low high-temperature storage capacity retention, and low 50-cycle capacity retention, i.e., poor cycle performance, severe aging loss, and low battery capacity and initial efficiency.
[0122] The negative electrode material prepared in Comparative Example 2 did not undergo a second carbon coating treatment. The I1 / I2 value was 0.95, and the y / x value was 0.43, indicating that very little lithium was protected by silicon or silicon oxide and the second carbon coating layer. During the pre-lithiation process, most of the lithium was doped on the surface of the negative electrode material, resulting in low high-temperature storage capacity retention and low 50-cycle capacity retention, i.e., poor cycle performance, severe aging loss, and low battery capacity and first-time efficiency.
[0123] Furthermore, both Examples 1-6 and Comparative Example 3 underwent two carbon coating processes, which protected some lithium from dissolution. The addition of hydrogen allowed the over-oxidized silicon to be reduced back to silicon, ultimately without affecting the battery's capacity and initial efficiency. Further, a comparison of the experimental data from Examples 1-6 with that from Comparative Example 3 shows that when I1 / I2 ≤ 0.3, the battery exhibits high capacity and initial efficiency while effectively suppressing aging losses and achieving a high 50-cycle capacity retention rate, indicating excellent cycle performance.
[0124] Furthermore, those skilled in the art should recognize that the above embodiments are merely illustrative of this application and are not intended to limit this application. Any appropriate changes and variations made to the above embodiments within the essential spirit and scope of this application fall within the scope of this application's disclosure.
Claims
1. A negative electrode material, characterized in that, The negative electrode material comprises a silicon-based core and a carbon layer coating the surface of the silicon-based core, wherein the silicon-based core comprises lithium silicate and silicon. The mass content of lithium detected in the first ICP measurement when a specified amount of the negative electrode material was digested with aqua regia was I1. In the second ICP measurement, the specified amount of the negative electrode material was digested using a mixture of HF and HNO3, heated until the solvent was completely evaporated, cooled, and then HCl was added. After heating until the residue was completely dissolved, the mass content of lithium element detected was I2, and I1 and I2 satisfied the following relationship: I1 / I2≤0.
3.
2. The negative electrode material according to claim 1, characterized in that, The range of lithium content I1 measured in the first ICP measurement is I1≤4wt%, and / or the range of lithium content I2 measured in the second ICP measurement is 2wt%≤I2≤13.5wt%.
3. The negative electrode material according to claim 1, characterized in that, The negative electrode material satisfies at least one of the following conditions: (1) The lithium silicate includes at least one of Li2SiO3 and Li2Si2O5; (2) Based on the mass of the negative electrode material, the mass content of lithium silicate in the negative electrode material is 20%~80%; (3) The silicon comprises silicon microcrystals, the size of which is ≤20nm.
4. The negative electrode material according to claim 1, characterized in that, The mass ratio of lithium to oxygen in the negative electrode material is set as x, and the mass ratio of lithium to oxygen in the surface layer of the negative electrode material is set as y. The relationship between x and y satisfies: y / x≤0.
35. The surface layer is defined as a layer with a thickness of ≤10nm from the outer surface of the negative electrode material particle to the center of the negative electrode material particle.
5. The negative electrode material according to claim 1, characterized in that, The negative electrode material satisfies at least one of the following conditions: (1) Based on the mass of the negative electrode material, the mass content of carbon in the negative electrode material is 2%~15%; (2) The pH value of the negative electrode material is in the range of 9 to 11.
6. The negative electrode material according to claim 1, characterized in that, The silicon-based core comprises silicon oxide, which includes silicon and oxygen elements, wherein the atomic ratio of silicon to oxygen is 0 to 2, excluding 0.
7. The negative electrode material according to claim 1, characterized in that, The silicon-based core comprises silicon oxide, which has the general chemical formula SiOx, where 0 < x ≤ 2.
8. A method for manufacturing a negative electrode material according to any one of claims 1 to 7, characterized in that, It possesses: Step S1: Perform the first carbon coating treatment on the silicon-oxygen raw material; Step S2: Perform surface oxidation treatment on the silicon-oxygen raw material that has undergone the first carbon coating; Step S3: Mix the surface-oxidized silicon-oxygen raw material with a lithium source and perform heat treatment to obtain lithium-doped silicon-oxygen raw material; as well as Step S4: Mix the lithium-doped silicon-oxygen raw material with a coating material containing a carbon source and a reducing gas, and perform a second carbon coating treatment to obtain the anode material.
9. The manufacturing method according to claim 8, characterized in that, The silicon-oxygen raw material is SiOy, where 0 < y ≤ 2.
10. A negative electrode sheet, characterized in that, It includes the negative electrode material according to any one of claims 1 to 7 or the negative electrode material obtained by the manufacturing method of the negative electrode material according to any one of claims 8 to 9.
11. A battery, characterized in that, Includes the negative electrode sheet as described in claim 10.
Citation Information
Patent Citations
Negative electrode active material, negative electrode comprising same, secondary battery comprising same, and method for preparing negative electrode active material
CN117397064A
Silicon-oxygen composite negative electrode material, preparation method thereof and lithium ion battery
TW202327151A